Electrophysical Properties of Ge–Sb–Te Thin Films for Phase Change Memory Devices; Russian Physics Journal; Vol. 59, iss. 9 - Lazarenko P. I. Petr Ivanovich; Kozyukhin S. A. Sergey Aleksandrovich; Sherchenkov A. A. Aleksey Anatoljevich; Babich A. V. Aleksey Valterovich; Timoshenkov S. P. Sergey Petrovich; Gromov D. G. Dmitry Gennadjevich; Zabolotskaya A. V. Anastasiya Vladimirovna; Kozik V. V. Vladimir Vasilievich (2017, 2017)
Title screen